Monitoring low-oxygen-adapted subsurface phytoplankton distribution in a changing ocean - Cox, Isabelle; Brewin, Robert J. W.; Sheen, Katy; Dall’Olmo, Giorgio; Ulloa, Osvaldo (Frontiers in Marine Science, 2024)
Recent decadal trends of deoxygenation in the global ocean interior have resulted in the expansion and shoaling of oxygen minimum zones (OMZs). When the OMZs upper bound nears the euphotic zone a unique community of phytoplankton, residing in extremely low light (<0.1% surface irradiance) and dissolved oxygen concentrations (<1-2 μmol kg-1), can appear. In this mini-review paper we synthesize our current understanding of the phytoplankton community that resides in an OMZ chlorophyll maximum (OMZ-CM), below the depths of the deep chlorophyll maximum found in permanently and seasonally stratified regions, and its role in OMZ biogeochemical cycles. Uncultivated basal lineages of the cyanobacterium Prochlorococcus dominate this community, forming an OMZ-CM that can contribute to integrated stocks of chlorophyll a, in some cases with a similar magnitude to the deep chlorophyll maximum. Photosynthesis by Prochlorococcus in the OMZ-CM provides a significant source of oxygen, that fuels the aerobic oxidation of nitrite and organic matter, impacting elemental biogeochemical cycling, including that of carbon and nitrogen. Yet, on a global scale, there is a lack of understanding and quantification of the spatial distribution of these OMZ-CM, their stocks of phytoplankton, their influence on fluxes of carbon and nitrogen, and how these may respond to climate change. Monitoring the dynamics of the OMZ-CM and biogeochemical cycles in OMZs is challenging, and requires a multidisciplinary approach, combining ship-based observations with autonomous platforms, satellite data, and conceptual models. Only then can the implications of enhanced deoxygenation on the future marine ecosystem be understood.